The clinical potential of functional magnetic resonance imaging. - Jezzard, P; Buxton, R (2006)
Functional magnetic resonance imaging (fMRI) has had a huge impact on understanding the healthy human brain. To date it has had much less impact in clinical neuroscience or clinical practice. The reasons for this are in part that the image acquisition, paradigm design, and data analysis strategies used presently are not sufficiently standardized. This makes the comparison of results across individuals, scanning sessions, and centers difficult. Nevertheless, there are emerging applications for clinical fMRI, and as the field matures the number of applications is likely to grow. It seems certain that fMRI has an important role to play in helping us understand the mechanisms of neuropsychiatric diseases and in helping to identify effective therapeutic strategies.